2018
DOI: 10.3390/met8121029
|View full text |Cite
|
Sign up to set email alerts
|

Non-Destructive Evaluation of Steel Surfaces after Severe Plastic Deformation via the Barkhausen Noise Technique

Abstract: This paper reports about the non-destructive evaluation of surfaces after severe shot peening via the Barkhausen noise technique. Residuals stresses and the corresponding Almen intensity, as well as microstructure alterations, are correlated with the Barkhausen noise signal and its extracted features. It was found that residual stresses as well as the Barkhausen noise exhibit a valuable anisotropy. For this reason, the relationship between the Barkhausen noise and stress state is more complicated. On the other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Increasing dislocation density increases the opposition against the DWs motion. On one hand, dislocation tangles, as pinning sites, preclude the DWs irreversible motion [ 14 , 22 , 23 , 24 ]. As soon as the pinning strength of dislocations is exceeded and DWs motion is initiated, the dislocations make shorter the free path of DWs motion, which in turn, also decreases MBN.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing dislocation density increases the opposition against the DWs motion. On one hand, dislocation tangles, as pinning sites, preclude the DWs irreversible motion [ 14 , 22 , 23 , 24 ]. As soon as the pinning strength of dislocations is exceeded and DWs motion is initiated, the dislocations make shorter the free path of DWs motion, which in turn, also decreases MBN.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the remarkable difference between XRD and MBN sensing depths, these techniques still can be considered as the near-surface techniques especially with respect of the sample thickness, which varies from 7.84 to 5.66 mm (see Table 2 ). Finally, it should be noticed that the contribution of residual stresses into evolution of MBN is limited (minor) and evolution of microstructure usually predominates in the case of Fe alloys [ 16 , 18 , 24 ]. Bozoroth [ 26 ] also found that the influence of lattice defects in iron-alloys usually predominates over the stress state.…”
Section: Discussionmentioning
confidence: 99%
“…This Special Issue published 33 high quality articles from 10 countries (according to the country of the corresponding author) with the number of contributions in brackets: China (22) , Japan (1) [23], Korea (1) [24], Canada (1) [25], Sweden (2) [26,27], Italy (1) [28], UK (1) [29], France (1) [30], Austria (1) [31], and Slovakia (2) [32,33]. This clearly reflects the enormous investment in R&D in China and the resultant outstanding outcomes to support its steel industry with~50% of global steel production.…”
Section: Contributionsmentioning
confidence: 99%
“…A paper co-authored by scientists from Sweden and Egypt (El-Tawil et al [26]) investigated the thermal devolatilisation of different bio-coals for the purpose of reducing fossil CO 2 emission in the steel industry. Other international collaborations include France-Canada-Albania (Kanari et al [30]), Slovakia-Czech Republic (Neslušan et al [33]), China-Ukraine (Cao et al [1]), and China-UK (Ge et al [2]).…”
Section: Contributionsmentioning
confidence: 99%
“…The result of the cyclic loading is the existence of the periodically generated loads acting against the frame. After a certain period, these loads may cause microscopic damage to the material; firstly, a gradually cumulative damage and cracking develop, which may result (together with other loads) in the breaking of a component [4,5].…”
Section: Introductionmentioning
confidence: 99%